Legal Protection for Child Defendants in Sexual Violence Cases - Hisyam, Akmal; Hasmiati, Rahmatullah Ayu; Pratama, Rio Arif (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: This research discusses legal protection aimed at child defendants, especially in cases of sexual violence committed against minors. This is based on a case study in Decision Number 13/Pid.Sus-Anak/2023/PNBPP and Decision Number 3/Pid.Sus-Anak/2023/PNBPP.Purposes of the Research: This research focuses on the stages or steps in the application of the law that protects the rights of child defendants with reference to Law Number 11 of 2012 concerning the Child Criminal Justice System.Methods of the Research: This research was conducted with a normative method in the form of a case study to evaluate the steps in the judiciary by starting with the arrest, investigation, prosecution, and conclusion with the welfare of children affected by the crime of sexual violence.Findings of the Research: The results of the study found that, although the criminal threat against perpetrators of sexual violence is quite severe, the implementation of punishment for children of sexual violence still prioritizes the principle of restorative justice, taking into account the psychological and social aspects of children. In both of the decisions analyzed, the child defendant received a prison sentence of different durations, and was required to undergo job training as part of the rehabilitation process. Legal protection for child defendants remains indispensable and plays an important role in guaranteeing the rights of every child as well as providing a deterrent effect in cases of sexual violence.